Modeling Teachers’ Use of Information Technologies during the Covid-19 Pandemic by the Technology Acceptance Model - ALTUN, Yener; DENİZ, Sinan (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Countries that attach importance to education make great investments in the field of educational technologies by reforming their education systems in this direction in order to raise dynamic individuals who can meet the needs of society, just like technology. It is undoubtedly teachers who will use these technologies in educational environments and transfer them to new generations. It is very important to reveal the factors that encourage or limit the use of these technologies in schools. In this study, the Technology Acceptance Model for Teachers (TAMT), which is the extended version of the Technology Acceptance Model (TAM), was used. Data analyzes were performed using the IBM AMOS V24 (Chicago, USA) program. Various statistical techniques such as descriptive statistics, multivariate statistical techniques and structural equation modeling were used in this study. The tested TAMT explained 54.6% of teachers’ behavioral intentions to use information technologies, 49.2% of their attitudes towards use, 27.7% of perceived usefulness, and 39.8% of perceived ease of use. Of the 32 hypotheses defined in TAMT, 11 were accepted as meaningless and 21 as significant.